(untitled) (Journal of the College of Basic Education, 2025)
This study addresses fuzzy initial value problems (FIVPs) to define initial conditions. We present numerical solutions for fuzzy differential equations using a modified two-step Simpson method and Runge-Kutta algorithms of orders 2–6, including convergence analysis. Computer programs generate approximate solutions, and we compare the performance of all methods through numerical examples.